Peran Dinas Kehutanan dalam Pengembangan Wisata Panorama Petung Sewu - Yuniar Ajeng Nara Pertiwi; Hendra Sukmana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The aim of the study was to analyze and describe the role of the East Java Provincial Forestry Service in developing the Panorama Petung Sewu Tourism in Mojokerto Regency. This research method is descriptive with a qualitative approach. Collection techniques using interviews, observation and documentation. Sources of data obtained through library research online and offline. The results of the study show that the government's role in the development of the Petung Sewu Panorama Tourism is still not fully successful, because the government only provides facilities in several objects such as building places of worship and pavilions, road repairs only in front of the tourist entrance and makeshift public toilet facilities, damaged photo spots and need renovation, cafes or stalls that are still not feasible. Apart from that, the lighting is still flowing to the Public Street Lighting (PJU) which will only turn on at certain times. The conclusion of this study is that the role of the East Java Provincial Forestry Service in the Development of Panorama Petung Sewu Tourism is not entirely of high quality and is achieved when considering 3 theoretical indicators regarding the government's role. Keywords: Development, Service Role, Tourism